PpePL1 and PpePL15 Are the Core Members of the Pectate Lyase Gene Family Involved in Peach Fruit Ripening and Softening - Xu, Ze; Dai, Jieyu; Kang, Tongyang; Shah, Kamran; Li, Qin; Liu, Kun; Xing, Libo; Ma, Juanjuan; Zhang, Dong; Zhao, Caiping (Frontiers in Plant Science, 2022)
Pectin is the major component in the primary cell wall and middle lamella, maintaining the physical stability and mechanical strength of the cell wall. Pectate lyase (PL), a cell wall modification enzyme, has a major influence on the structure of pectin. However, little information and no comprehensive analysis is available on the PL gene family in peach (Prunus persica L. Batsch). In this study, twenty PpePL genes were identified in peach. We characterized their physicochemical characteristics, sequence alignments, chromosomal locations, and gene structures. The PpePL family members were classified into five groups based on their phylogenetic relationships. Among those, PpePL1, 9, 10, 15, and 18 had the higher expression abundance in ripe fruit, and PpePL1, 15, and 18 were up-regulated during storage. Detailed RT-qPCR analysis revealed that PpePL1 and PpePL15 were responsive to ETH treatment (1 g L-1 ethephon) with an abundant transcript accumulation, which suggested these genes were involved in peach ripening and softening. In addition, virus-induced gene silencing (VIGS) technology was used to identify the roles of PpePL1 and PpePL15. Compared to controls, the RNAi fruit maintained greater firmness in the early storage stage, increased acid-soluble pectin (ASP), and reduced water-soluble pectin (WSP). Moreover, transmission electron microscopy (TEM) showed that cell wall degradation was reduced in the fruit of RNAi-1 and RNAi-15, which indicated that softening of the RNAi fruit has been delayed. Our results indicated that PpePL1 and PpePL15 play an important role in peach softening by depolymerizing pectin and degrading cell wall.